Mixed-dimension clay mineral diaphragm as well as preparation method and application thereof

By mixing one-dimensional and two-dimensional tanned soil minerals and preparing the separator through electrospinning technology, the problem of insufficient thermal stability and mechanical properties of the separator of lithium-ion batteries is solved, and battery performance with high specific capacity and safety is achieved.

CN119651046AActive Publication Date: 2025-03-18CHINA UNIV OF MINING & TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411829900.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-18
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

The existing lithium-ion battery separators have problems such as poor wetting, poor thermal stability and easy puncture by lithium dendrites, which affect the safety and performance of the battery.

Method used

A mixture of one-dimensional and two-dimensional clay minerals is used as the main component of the separator, and a nanofiber membrane is prepared by electrospinning technology, and a mixed clay mineral membrane is obtained by vacuum drying.

Benefits of technology

It improves the thermal stability and mechanical properties of the diaphragm, inhibits the growth of lithium dendrites, guarantees the safety of the battery, and achieves battery performance with high specific capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119651046A_ABST
    Figure CN119651046A_ABST
Patent Text Reader

Abstract

The invention discloses a mixed-vitamin clay mineral diaphragm as well as a preparation method and application thereof. Dispersing a multidimensional clay mineral formed by mixing a one-dimensional clay mineral and a two-dimensional clay mineral and an organic matter matrix into a solvent according to a mass ratio of (1: 15)-(1: 1), and heating and stirring until the slurry is uniform to obtain an electrospinning solution; transferring the electrospinning liquid into a needle propeller of an electrostatic spinning machine, setting electrostatic spinning parameters, and carrying out electrostatic spinning to obtain a nanofiber membrane; and carrying out vacuum drying on the nanofiber membrane to prepare the mixed-dimension clay mineral diaphragm. The diaphragm can be used for assembling a lithium ion battery. The clay mineral used in the invention has the advantages of stable physical and chemical properties, developed pore structure and low price, and the prepared mixed-dimension clay mineral diaphragm has excellent thermal stability and mechanical properties, and can ensure the safety of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new materials, and in particular to a mixed-dimensional clay mineral diaphragm and a preparation method and application thereof. Background Art

[0002] The development of renewable clean energy such as wind power, hydropower, and solar energy is conducive to the implementation of the dual-carbon strategy. However, these clean energy sources are intermittent and volatile in time or space, which limits their large-scale application. Therefore, new energy storage devices have emerged. Lithium-ion batteries are widely used in many fields such as portable electronic devices (such as smartphones, laptops and tablets), electric vehicles (EVs), hybrid electric vehicles (HEVs), energy storage systems (ESSs), and drones due to their high energy density, long cycle life, no memory effect, low self-discharge rate, and environmental protection. The main components of lithium-ion batteries include: positive electrode, negative electrode, electrolyte, and diaphragm. As an important component of lithium-ion batteries, the diaphragm not only isolates the positive and negative electrodes to avoid direct contact between the positive and negative electrodes, but also provides a transmission channel for the back and forth migration of lithium ions between the positive and negative electrodes. Commercial polyolefin diaphragms have problems such as poor electrolyte wettability, poor thermal stability, and easy penetration by lithium dendrites. Therefore, it is important to develop diaphragms with excellent thermal stability, mechanical properties, and electrolyte wettability to ensure the normal operation and safety of batteries.

[0003] Natural clay minerals have the advantages of excellent thermal stability, mechanical properties, developed pore structure, wide sources, low price, and green environmental protection. They have great advantages in being used in lithium-ion battery separators. Among them, one-dimensional clay minerals can not only improve thermal stability, but their unique fibrous or rod-like morphology can also significantly enhance the mechanical properties of the organic matrix, thereby improving the mechanical properties of the separator and effectively avoiding piercing by lithium dendrites; two-dimensional clay minerals are lamellar, and cation exchange can be achieved between their layers, which is conducive to the storage and rapid migration of lithium ions. At the same time, the two-dimensional lamellar layer can inhibit the growth of lithium dendrites. Therefore, the mixed-dimensional clay mineral separator mixed with one-dimensional and two-dimensional clay minerals not only has excellent thermal stability and mechanical properties, but also can inhibit the growth of lithium dendrites, thereby ensuring the safety of the battery. Summary of the invention

[0004] One of the purposes of the present invention is to provide a method for preparing a mixed-dimensional clay mineral diaphragm.

[0005] The second object of the present invention is to provide a mixed-dimensional clay mineral diaphragm obtained by the above preparation method.

[0006] The third object of the present invention is to provide the application of the above-mentioned mixed-dimensional clay mineral membrane.

[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0008] In a first aspect, the present invention provides a method for preparing a mixed-dimensional clay mineral membrane, comprising the following steps:

[0009] Step (1), dispersing clay mineral and organic matrix in a solvent at a mass ratio of 1:15-1:1, controlling the spinning concentration to be 15-20wt%, heating and stirring until the slurry is uniform, and obtaining an electrospinning liquid; the clay mineral is a mixture of a one-dimensional clay mineral and a two-dimensional clay mineral;

[0010] Step (2), transferring the electrospinning liquid into the needle propeller of the electrospinning machine, setting the electrospinning parameters, and performing electrospinning to obtain a nanofiber membrane;

[0011] Step (3), vacuum drying the nanofiber membrane to obtain a mixed-dimensional clay mineral membrane.

[0012] Preferably, in step (1), the one-dimensional clay mineral is one of brucite, halloysite, attapulgite, and sepiolite; and the two-dimensional clay mineral is one of mica, montmorillonite, kaolin, vermiculite, and hydrotalcite.

[0013] Preferably, in step (1), the mass ratio of the one-dimensional clay mineral to the two-dimensional clay mineral is 0.5:10-10:0.5.

[0014] Preferably, in step (1), the organic matrix is ​​at least one of sodium alginate, water-soluble chitosan, chitosan, cellulose acetate, polylactic acid, polyethylene oxide, polyvinyl acetate, polyethylene glycol, polyurethane, polyvinylidene fluoride, polyimide, polyamide, polyethylene terephthalate, polyvinyl pyrrolidone, polyacrylonitrile, polymethyl methacrylate, and polycarbonate.

[0015] Preferably, in step (1), the solvent is at least one of dichloromethane, ethanol, formic acid, acetic acid, deionized water, and N,N-dimethylformamide.

[0016] Preferably, in step (1), the temperature of the heating and stirring is 50°C-95°C.

[0017] Preferably, in step (2), the electrospinning parameters are: voltage of 10-25 kV, syringe propulsion speed of 0.05-5 mL / h, receiving distance of 15-20 cm, and drum speed of 50-800 rpm.

[0018] Preferably, in step (3), the vacuum drying is carried out at a temperature of 50°C-90°C and for a time of 10-24 hours.

[0019] In a second aspect, the present invention provides a mixed-dimensional clay mineral diaphragm prepared by the above preparation method.

[0020] The morphology of the mixed-dimensional clay mineral diaphragm prepared by the present invention presents the characteristics of one-dimensional columnar and two-dimensional flaky clay minerals wrapped in fibers.

[0021] In a third aspect, the present invention further provides a lithium-ion battery, wherein the lithium-ion battery comprises the above-mentioned mixed-dimensional clay mineral diaphragm.

[0022] The button battery was assembled using the existing method, and its physical, chemical and battery performance were tested; lithium iron phosphate, conductive carbon black and PVDF were added to DMF in a mass ratio of 8:1:1, stirred evenly and coated on aluminum foil, vacuum dried and cut into 16mm discs as the positive electrode, the prepared mixed-dimensional clay mineral membrane as the membrane, the lithium sheet as the negative electrode, 1M LiPF6 as the electrolyte, and the half-cell was assembled.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] (1) The mixed-dimensional clay mineral membrane prepared by the present invention has a high specific capacity.

[0025] (2) The mixed-dimensional clay mineral diaphragm prepared by the present invention has excellent thermal stability and mechanical properties, which can ensure the safety of the battery. Among them, in addition to improving the thermal stability, the one-dimensional clay minerals can also significantly enhance the mechanical properties of the organic matrix with their unique fibrous or rod-like morphology, thereby improving the mechanical properties of the diaphragm and effectively avoiding being pierced by lithium dendrites; the two-dimensional clay minerals are lamellar, and cation exchange can be achieved between the layers, which is beneficial to the storage and rapid migration of lithium ions. At the same time, the two-dimensional lamellae can inhibit the growth of lithium dendrites. Therefore, the mixed-dimensional clay mineral diaphragm mixed with one-dimensional and two-dimensional clay minerals not only has excellent thermal stability and mechanical properties, but also can inhibit the growth of lithium dendrites, thereby ensuring the safety of the battery.

[0026] (3) The clay minerals used in the present invention have the advantages of excellent thermal stability, mechanical properties, chemical stability, developed pore structure, low price, environmental friendliness, and wide sources, which are conducive to the development of high-performance, low-cost diaphragms. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is a schematic diagram of the process of preparing a mixed-dimensional clay mineral diaphragm according to the present invention;

[0028] Figure 2 is a scanning electron microscope image of a mixed-dimensional clay mineral diaphragm prepared in Example 1 of the present invention;

[0029] Figure 3 is a transmission electron microscope image of a mixed-dimensional clay mineral diaphragm prepared in Example 1 of the present invention;

[0030] Figure 4It is the thermal stability diagram of the clay mineral diaphragm obtained in Examples 1 to 4 of the present invention, Comparative Examples 1-2, and Celgard 2500;

[0031] Figure 5 It is a rate performance diagram of the clay mineral diaphragms prepared in Examples 1 to 4 of the present invention, Comparative Examples 1-2, and Celgard 2500. DETAILED DESCRIPTION

[0032] The present invention provides a method for preparing a mixed-dimensional clay mineral diaphragm, the process of which is as follows: Figure 1 As shown, the following steps are included:

[0033] Step (1), dispersing clay mineral and organic matrix in a solvent at a mass ratio of 1:15-1:1, controlling the spinning concentration to be 18%, heating and stirring until the slurry is uniform, and obtaining an electrospinning liquid; the clay mineral is a mixture of a one-dimensional clay mineral and a two-dimensional clay mineral;

[0034] Step (2), transferring the electrospinning liquid into the needle propeller of the electrospinning machine, setting the electrospinning parameters, and performing electrospinning to obtain a nanofiber membrane;

[0035] Step (3), vacuum drying the nanofiber membrane to obtain a mixed-dimensional clay mineral membrane.

[0036] The present invention is further described in detail below with reference to the accompanying drawings and specific examples. The experimental methods used in the following examples are conventional methods unless otherwise specified; the reagents, materials, etc. used in the following examples are all commercially available unless otherwise specified.

[0037] Example 1

[0038] This embodiment relates to a method for preparing a mixed-dimensional clay mineral membrane, comprising the following steps:

[0039] Step (1), adding 0.0192 g of attapulgite and 0.0768 g of montmorillonite to 11.4 mL of NN dimethylformamide, and ultrasonicating for 1 h; after ultrasonicating, adding 1.2 g of polyvinylidene fluoride, and continuously stirring for 22 h under heating conditions at 50° C. in a water bath, to obtain a light brown viscous electrospinning liquid.

[0040] Step (2), transfer the electrospinning liquid obtained in step (1) into the electrospinning syringe for electrospinning (the electrospinning parameters are set as follows: spinning liquid amount: 5 mL, applied positive voltage: 15 kV, negative voltage: 0 kV, injection speed 1 mL / h, receiving roller speed: 300 rpm, spinning time 5 h) to obtain a nanofiber membrane.

[0041] Step (3), removing the nanofiber membrane obtained in step (2) from the silicone oil paper and placing it in a vacuum drying oven at a constant temperature of 60°C for 12 hours of vacuum drying to ensure that the residual solvent is completely removed, and finally obtaining a mixed-dimensional clay mineral membrane (A2M8).

[0042] The scanning electron microscope and transmission electron microscope images of the mixed-dimensional clay mineral membrane prepared in this embodiment are shown in FIG. Figure 2 and Figure 3 As shown. Figure 2 It can be seen that the synthesized diaphragm presents a network structure in which fibers are stacked and interlaced. Figure 3 It can be seen that a single fiber of the mixed-dimensional clay mineral separator contains one-dimensional columnar and two-dimensional flaky clay minerals. In addition to improving thermal stability, the one-dimensional clay minerals can also significantly enhance the mechanical properties of the organic matrix with their unique fibrous or rod-like morphology, thereby improving the mechanical properties of the separator and effectively avoiding being pierced by lithium dendrites; the two-dimensional clay minerals are lamellar, and cation exchange can be achieved between the layers, which is beneficial to the storage and rapid migration of lithium ions. At the same time, the two-dimensional lamellar layers can inhibit the growth of lithium dendrites, indicating that the present embodiment has produced a mixed-dimensional clay mineral separator.

[0043] Example 2

[0044] This embodiment relates to a method for preparing a mixed-dimensional clay mineral membrane, comprising the following steps:

[0045] Step (1), adding 0.0384 g of attapulgite and 0.0576 g of montmorillonite to 11.4 mL of NN dimethylformamide, and ultrasonicating for 1 h; after ultrasonicating, adding 1.2 g of polyvinylidene fluoride, and continuously stirring for 22 h under heating conditions at 50° C. in a water bath, to obtain a light brown viscous electrospinning liquid.

[0046] Step (2), transfer the electrospinning liquid obtained in step (1) into the electrospinning syringe for electrospinning (the electrospinning parameters are set as follows: spinning liquid amount: 5 mL, applied positive voltage: 15 kV, negative voltage: 0 kV, injection speed 1 mL / h, receiving roller speed: 300 rpm, spinning time 5 h) to obtain a nanofiber membrane.

[0047] Step (3), removing the nanofiber membrane obtained in step (2) from the silicone oil paper and placing it in a vacuum drying oven at a constant temperature of 60°C for 12 hours of vacuum drying to ensure that the residual solvent is completely removed, and finally obtaining a mixed-dimensional clay mineral membrane (A4M6).

[0048] Example 3

[0049] This embodiment relates to a method for preparing a mixed-dimensional clay mineral membrane, comprising the following steps:

[0050] Step (1), adding 0.0576 g of attapulgite and 0.0384 g of montmorillonite to 11.4 mL of NN dimethylformamide, and ultrasonicating for 1 h; after ultrasonicating, adding 1.2 g of polyvinylidene fluoride, and continuously stirring for 22 h under heating conditions at 50° C. in a water bath, to obtain a light brown viscous electrospinning liquid.

[0051] Step (2), transfer the electrospinning liquid obtained in step (1) into the electrospinning syringe for electrospinning (the electrospinning parameters are set as follows: spinning liquid amount: 5 mL, applied positive voltage: 15 kV, negative voltage: 0 kV, injection speed 1 mL / h, receiving roller speed: 300 rpm, spinning time 5 h) to obtain a nanofiber membrane.

[0052] Step (3), removing the nanofiber membrane obtained in step (2) from the silicone oil paper and placing it in a vacuum drying oven at a constant temperature of 60°C for 12 hours of vacuum drying to ensure that the residual solvent is completely removed, and finally obtaining a mixed-dimensional clay mineral membrane (A6M4).

[0053] Example 4

[0054] This embodiment relates to a method for preparing a mixed-dimensional clay mineral membrane, comprising the following steps:

[0055] Step (1), adding 0.0768 g of attapulgite and 0.0192 g of montmorillonite to 11.4 mL of NN dimethylformamide, and ultrasonicating for 1 h; after ultrasonicating, adding 1.2 g of polyvinylidene fluoride, and continuously stirring for 22 h under heating conditions at 50° C. in a water bath, to obtain a light brown viscous electrospinning liquid.

[0056] Step (2), transfer the electrospinning liquid obtained in step (1) into the electrospinning syringe for electrospinning (the electrospinning parameters are set as follows: spinning liquid amount: 5 mL, applied positive voltage: 15 kV, negative voltage: 0 kV, injection speed 1 mL / h, receiving roller speed: 300 rpm, spinning time 5 h) to obtain a nanofiber membrane.

[0057] Step (3), remove the nanofiber membrane obtained in step (2) from the silicone oil paper and place it in a vacuum drying oven at a constant temperature of 60°C for 12 hours of vacuum drying to ensure that the residual solvent is completely removed, and finally obtain a mixed-dimensional clay mineral membrane (A8M2).

[0058] Comparative Example 1

[0059] This comparative example relates to a method for preparing a mixed-dimensional clay mineral diaphragm, comprising the following steps:

[0060] Step (1), adding 0.096 g of attapulgite to 11.4 mL of NN dimethylformamide, and ultrasonicating for 1 h; after ultrasonicating, adding 1.2 g of polyvinylidene fluoride, and continuously stirring for 22 h under heating conditions at 50° C. in a water bath, to obtain a light brown viscous electrospinning liquid.

[0061] Step (2), transfer the electrospinning liquid obtained in step (1) into the electrospinning syringe for electrospinning (the electrospinning parameters are set as follows: spinning liquid amount: 5 mL, applied positive voltage: 15 kV, negative voltage: 0 kV, injection speed 1 mL / h, receiving roller speed: 300 rpm, spinning time 5 h) to obtain a nanofiber membrane.

[0062] Step (3), removing the nanofiber membrane obtained in step (2) from the silicone oil paper and placing it in a vacuum drying oven at a constant temperature of 60°C for 12 hours of vacuum drying to ensure that the residual solvent is completely removed, and finally obtaining a mixed-dimensional clay mineral membrane (A10M0).

[0063] Comparative Example 2

[0064] This comparative example relates to a method for preparing a mixed-dimensional clay mineral diaphragm, comprising the following steps:

[0065] Step (1), adding 0.096 g of montmorillonite to 11.4 mL of NN dimethylformamide, and ultrasonicating for 1 h; after ultrasonicating, adding 1.2 g of polyvinylidene fluoride, and continuously stirring for 22 h under heating conditions at 50° C. in a water bath, to obtain a light brown viscous electrospinning liquid.

[0066] Step (2), transfer the electrospinning liquid obtained in step (1) into the electrospinning syringe for electrospinning (the electrospinning parameters are set as follows: spinning liquid amount: 5 mL, applied positive voltage: 15 kV, negative voltage: 0 kV, injection speed 1 mL / h, receiving roller speed: 300 rpm, spinning time 5 h) to obtain a nanofiber membrane.

[0067] Step (3), removing the nanofiber membrane obtained in step (2) from the silicone oil paper and placing it in a vacuum drying oven at a constant temperature of 60°C for 12 hours of vacuum drying to ensure that the residual solvent is completely removed, and finally obtaining a mixed-dimensional clay mineral membrane (A0M10).

[0068] Thermal stability test

[0069] The clay mineral membranes prepared in Examples 1 to 4 and Comparative Examples 1-2 and Celgard 2500 were cut into 19 mm discs by a punching machine, and placed in an oven at 180°C for heat treatment for 0.5 h to test their thermal stability. Figure 4It can be seen that the clay mineral membranes prepared in Examples 1 to 4 and Comparative Examples 1-2 still maintained their shape and size when heat treated at 180°C, with almost no shrinkage, while the Celgard 2500 membrane shrank over a large area, and its original circular shape completely disappeared, presenting a spindle shape. This indicates that the addition of clay minerals can significantly improve the thermal stability of the membrane, thereby making the clay mineral membrane have excellent thermal stability, further ensuring the safety of the battery.

[0070] Rate performance test

[0071] Lithium iron phosphate, conductive carbon black and PVDF were added to DMF in a mass ratio of 8:1:1, stirred evenly and coated on aluminum foil. After vacuum drying, they were cut into 16 mm discs as the positive electrode, lithium sheet as the negative electrode, 1M LiPF6 as the electrolyte, and the clay mineral membranes prepared in Examples 1 to 4 and Comparative Examples 1-2 and Celgard2500 membranes were assembled into half-cells to test their rate performance. Figure 5 Table 1 is a rate performance diagram of the prepared mixed-dimensional clay mineral diaphragm. At 0.2C, the half-cell specific capacity of the diaphragm assembly of Example 1 is 164.4 mAh / g, the half-cell specific capacity of the diaphragm assembly of Example 2 is 155.3 mAh / g, the half-cell specific capacity of the diaphragm assembly of Example 3 is 159.9 mAh / g, the half-cell specific capacity of the diaphragm assembly of Example 4 is 154.9 mAh / g, the half-cell specific capacity of the diaphragm assembly of Comparative Example 1 is 153.4 mAh / g, and the half-cell specific capacity of the diaphragm assembly of Comparative Example 2 is 159.5 mAh / g. It can be seen that the mixed-dimensional clay mineral diaphragm (Example 1) has the highest specific capacity, and its specific capacity is higher than the specific capacity of the single-dimensional clay mineral diaphragm (Comparative Example 1 and Comparative Example 2), which shows that the introduction of mixed-dimensional clay minerals has better battery performance than the clay mineral diaphragm prepared by adding single-dimensional clay minerals. In addition, it can be seen that when the discharge rate is restored from 2C to 0.2C, the batteries all show excellent recovery ability, and the discharge specific capacity is almost close to the initial specific capacity.

[0072] Table 1 Battery rate performance (unit: mAh / g)

[0073]

[0074]

[0075] The mixed-dimensional clay mineral diaphragm prepared by the embodiment of the present invention has a high specific capacity. In addition to improving thermal stability, the one-dimensional clay mineral in the mixed-dimensional clay mineral diaphragm can also significantly enhance the mechanical properties of the organic matrix with its unique fibrous or rod-like morphology, thereby improving the mechanical properties of the diaphragm and effectively avoiding being pierced by lithium dendrites; at the same time, the two-dimensional clay mineral is in a lamellar shape, and cation exchange can be achieved between its layers, which is beneficial to the storage and rapid migration of lithium ions, and the two-dimensional lamellae can inhibit the growth of lithium dendrites. Therefore, the mixed-dimensional clay mineral diaphragm mixed with one-dimensional and two-dimensional clay minerals not only has excellent thermal stability and mechanical properties, but also can inhibit the growth of lithium dendrites, thereby ensuring the safety of the battery. The clay minerals used in the present invention are inexpensive, environmentally friendly, and widely available, which is conducive to the development of high-performance, low-cost diaphragms.

[0076] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any modifications, equivalent substitutions and improvements made by any technician familiar with the technical field within the technical scope disclosed by the present invention and within the spirit and principle of the present invention should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a mixed-dimensional clay mineral membrane, characterized in that: The following steps are involved: Step (1), dispersing clay mineral and organic matrix in a solvent at a mass ratio of 1:15-1:1, controlling the spinning concentration to be 15-20wt%, heating and stirring until the slurry is uniform, and obtaining an electrospinning liquid; the clay mineral is a mixture of a one-dimensional clay mineral and a two-dimensional clay mineral; Step (2), transferring the electrospinning liquid into the needle propeller of the electrospinning machine, setting the electrospinning parameters, and performing electrospinning to obtain a nanofiber membrane; Step (3), vacuum drying the nanofiber membrane to obtain a mixed-dimensional clay mineral membrane.

2. The method for preparing a mixed-dimensional clay mineral membrane according to claim 1, characterized in that: In step (1), the one-dimensional clay mineral is one of brucite, halloysite, attapulgite, and sepiolite; and the two-dimensional clay mineral is one of mica, montmorillonite, kaolin, vermiculite, and hydrotalcite.

3. The method for preparing a mixed-dimensional clay mineral membrane according to claim 1, characterized in that: In step (1), the mass ratio of the one-dimensional clay mineral to the two-dimensional clay mineral is 0.5:10-10:0.

5.

4. The method for preparing a mixed-dimensional clay mineral membrane according to claim 1, characterized in that: In step (1), the organic matrix is ​​at least one of sodium alginate, water-soluble chitosan, chitosan, cellulose acetate, polylactic acid, polyethylene oxide, polyvinyl acetate, polyethylene glycol, polyurethane, polyvinylidene fluoride, polyimide, polyamide, polyethylene terephthalate, polyvinyl pyrrolidone, polyacrylonitrile, polymethyl methacrylate, and polycarbonate.

5. The method for preparing a mixed-dimensional clay mineral membrane according to claim 1, characterized in that: In step (1), the solvent is at least one of dichloromethane, ethanol, formic acid, acetic acid, deionized water, and N,N-dimethylformamide.

6. The method for preparing a mixed-dimensional clay mineral membrane according to claim 1, characterized in that: In step (1), the temperature of the heating and stirring is 50°C-95°C.

7. The method for preparing a mixed-dimensional clay mineral membrane according to claim 1, characterized in that: In step (2), the electrospinning parameters are: voltage of 10-25 kV, syringe propulsion speed of 0.05-5 mL / h, receiving distance of 15-20 cm, and drum speed of 50-800 rpm.

8. The method for preparing a mixed-dimensional clay mineral membrane according to claim 1, characterized in that: In step (3), the vacuum drying is carried out at a temperature of 50°C-90°C and for a time of 10-24 hours.

9. A mixed-dimensional clay mineral diaphragm, characterized in that: The method is prepared according to any one of claims 1 to 8.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the mixed-dimensional clay mineral separator according to claim 9.

Citation Information

Patent Citations

  • In-situ inorganic-organic composite spinning diaphragm as well as preparation method and application thereof

    CN113140868A

  • Double-layer composite diaphragm, preparation method and HNTs coated PI-PP double-layer composite diaphragm

    CN115149211A

  • Lithium ion secondary battery

    JP2014060123A

  • Sheet-typed Separator Coated with Clay Mineral andLithium Electrochemical Cell Employing the Same

    KR1020080017110A